Mediality, temporality, social cognition, and evolution - Blanco Rivero, José Javier (2019)
In the literature of Media Studies, the word mediality has emerged as an expression of the concern about the specificity of media and their link to time, experience, technology and social change. However, mediality is not yet a concept, since the description of the function of media as mediation and transmission has become an obstacle to achieve further developments. In light of these remarks, this paper proposes a theoretical arrangement that gives meaning to mediality by connecting the word into a network of concepts, such as social cognition, evolution, temporality, synchronization and double closure. In order to achieve this goal, the author designs a theoretical apparatus consisting of the self-referential coupling between N. Luhmann’s systems theory, H. von Foerster’s second order cybernetics, R. Harris’ integration linguistics, and A. Clark’s extended cognition. A consistent integration and interpretation of the sketched theory, allows us to draw the conclusion that in order to comprehend mediality, it is crucial to understand the relationship between information, double closure, social cognition and evolution, while questions regarding human cognition do not be to be involved; and if that should be the case, research should depart from the problem of the structural coupling between human and social cognition.